Detecting shifts in tropical moisture imbalances with satellite‐derived isotope ratios in water vapor. Issue 11 (10th June 2017) - Bailey, A.; Blossey, P. N.; Noone, D.; Nusbaumer, J.; Wood, R.
Abstract: As global temperatures rise, regional differences in evaporation ( E ) and precipitation ( P ) are likely to become more disparate, causing the drier E ‐dominated regions of the tropics to become drier and the wetter P ‐dominated regions to become wetter. Models suggest that such intensification of the water cycle should already be taking place; however, quantitatively verifying these changes is complicated by inherent difficulties in measuring E and P with sufficient spatial coverage and resolution. This paper presents a new metric for tracking changes in regional moisture imbalances (e.g., E ‐ P ) by defining δ D q —the isotope ratio normalized to a reference water vapor concentration of 4 mmol mol −1 —and evaluates its efficacy using both remote sensing retrievals and climate model simulations in the tropics. By normalizing the isotope ratio with respect to water vapor concentration, δ D q isolates the portion of isotopic variability most closely associated with shifts between E ‐ and P ‐dominated regimes. Composite differences in δ D q between cold and warm phases of El Niño–Southern Oscillation (ENSO) verify that δ D q effectively tracks changes in the hydrological cycle when large‐scale convective reorganization takes place. Simulated δ D q also demonstrates sensitivity to shorter‐term variability in E ‐ P at most tropical locations. Since the isotopic signal of E ‐ P in free tropospheric water vapor transfers to the isotope ratios of precipitation, multidecadal observations of both water vapor and precipitation isotope ratios should provide key evidence of changes in regional moisture imbalances now and in the future. Key Points: Normalizing the water vapor isotope ratio with respect to water vapor concentration creates a new metric to track convective reorganization This new metric isolates isotopic variability caused by shifting imbalances between tropical precipitation and evaporation Since isotope ratios can be retrieved from remote sensing, variations in water cycle intensity can be investigated globally